Islam Nusantara (Sebuah Konsep Pendidikan Beragama Secara Moderat) - Rahmat Sholihin; Amelia Rahmaniah (PT. Sharia Journal and Education Center, 2024)
Abstract The issue of Islam Nusantara has become a new discourse for Muslims in Indonesia, a new offer in the concept of moderate religious education. Various groups have spoken out in response to this issue. Initially raised by NU clerics, it was responded to variously by Indonesian Muslims. Within NU itself there is debate, as well as among Muhammadiyah. The identity of